Enhancing elementary students' motivation in IPAS through qreatif app-assisted deep learning approach - Melkior Ronaldo Repe; Ana Fitrotun Nisa; Akbar Al Masjid (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2026)
Science and Social Studies (IPAS) learning in elementary schools faces challenges regarding student engagement due to teacher-centered practices. This study aims to describe the implementation of Deep Learning assisted by the Qreatif application and analyze its impact on students' learning motivation within the Merdeka Curriculum framework. Using a qualitative descriptive approach, the study involved fourth-grade elementary students. Data were collected through observations, interviews, and documentation, then analyzed using data condensation, data display, and conclusion drawing. The findings demonstrate that the integration of the Qreatif application into the Deep Learning model significantly enhances students' motivation, as evidenced by increased interest, active participation, and learning autonomy. The interactive visualization and explorative activities in Qreatif strengthen conceptual understanding and foster intrinsic motivation. These findings offer practical implications for developing technology-based learning that aligns with the principles of authentic and reflective pedagogy in the Merdeka Curriculum.